Group taxation of tightly-held qualifying groups in South Africa - Adams, Razeen (Department of Finance and Tax, 2020)
Currently, companies are taxed on an individual basis in South Africa and there is no provision for the offsetting of profits and losses of different companies within a tax group. Admittedly, businesses have the option to operate under a single divisionalised entity whereby they are able to enjoy offsetting profit and losses of trades of different divisions within such an entity. There are however, strong business reasons as to why businesses split themselves into separate legal entities. The most noteworthy benefit being the ability to manage business risk through limited liability provisions contained in corporate legislation. Arguments have been put forward to the effect that groups, although legally separated through different corporate entities, operate in much the same way as a divisionalised single entity business does. The current tax treatment, which taxes entities of a group on their individual taxable incomes, is therefore argued to not provide a true assessment of the group’s tax position. Arguments in the Margo Commission of Inquiry report have even gone as far as saying that it seems unfair to tax profitable entities in a group while the overall taxable income of the group may be negative. With the above in mind, the question of whether a group tax system would be suitable for implementation in South Africa is brought to the table. As will be seen in this dissertation, there are strong opinions on either side of determining whether a group tax system would be appropriate for South Africa. Opinions in favour of a group tax system view the system as a potential tool to encourage business through more favourable tax conditions thereby encouraging growth and development of the economy. Drawbacks of the system include the perceived loss to the fiscus as tax relief is provided while concerns have also been raised relating to the current ability of the South African Revenue Service (SARS) to cope with the implementation of such a change to legislation. The author of this dissertation acknowledges the need for South Africa to maximise its revenue collection to meet its budgetary obligations. However, at the same time, the author is of the view that government should look to creating environments in which smaller businesses may develop and grow, potentially increasing revenue collection in the long run in any event. For these reasons, the author has taken a conservative approach to explore the idea of providing for a group tax system for tightly‐ held tax groups with a limited turnover. This could potentially have the effect of developing small businesses while limiting the exposure of the fiscus to a revenue collection reduction. Loosely defined, tightly‐held groups of companies refer to groups where there is a close relation between shareholders of the group. Further to this, the author highlights the challenges that small businesses face in moving towards a group structure to derive the benefits that have been identified in this dissertation. With that in mind, the author has looked to encouraging group formation in small businesses by attempting to relieve some of the challenges that small businesses encounter in trying to establish a group structure. Through this dissertation, the author proposes a group tax system whereby only tightly‐held qualifying groups will be allowed to participate. The proposal contained within the dissertation has been drafted after assessing the findings of the preceding chapters as well as adapting some of the implementation provisions provided by the United Kingdom (UK) and the United States of America (USA) tax legislation. This ability to produce a suitable proposal for implementation in South Africa will be a step towards concluding on whether South African tax legislators should be looking to implement a group tax system whereby tightly‐held groups of companies will be the initial qualifying audience. The conclusion drawn through the research conducted is that steps should be taken towards the implementation of group tax for tightly‐held groups of companies. A stumbling block, however, as identified in the interim Nugent Commission report, is the current state that SARS finds itself in. It would seem reckless to recommend the instatement of a provision of this stature while SARS is in its current state. It is thus concluded, that movement towards a group tax system for tightly‐held groups of companies should be delayed until such time that SARS has re‐established itself as a proficient organ of the state.